(untitled) (Polifonia, 2013)
RESUMO: Na obra She tries her tongue, her silence softly breaks (1989),da escritora afro-caribenha Marlene Nourbese Philip, o leitor é confrontadocom uma das consequências da diáspora africana para as Américas:o silenciamento e o não-pertencimento construídos socialmente pormeio da língua inglesa. Nesse sentido, analisaremos, em nosso artigo, aprática discursiva da autora em questão e sua contextualização na históriadiaspórica como estratégia de reversão do discurso do dominadorpela (re)versão da palavra. PALAVRAS-CHAVE: diáspora, silêncio, poética, linguagem ABSTRACT: In the book She tries her tongue, her silence softly breaks(1989), written by Afro-Caribbean writer Marlene Nourbese Philip, thereader is confronted with one of the consequences of the African diasporato the Americas: the silencing and not belonging, which were sociallyconstructed through the English language. In this sense, our paper willexamine the discursive practice of the author and its contextualizationin the diasporic history as a strategy for reversing the discourse of thedominant power by the (re)version of the word. KEYWORDS: diaspora, silence, poetics, language